2016
DOI: 10.1103/physreve.94.033104
|View full text |Cite
|
Sign up to set email alerts
|

Water retention against drying with soft-particle suspensions in porous media

Abstract: Polymers suspended in granular packings have a significant impact on water retention, which is important for soil irrigation and the curing of building materials. Whereas the drying rate remains constant during a long period for pure water due to capillary flow providing liquid water to the evaporating surface, we show that it is not the case for a suspension made of soft polymeric particles called microgels: The drying rate decreases immediately and significantly. By measuring the spatial water saturation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Under this assumption, after some transient stage, the drying rate would be controlled by vapor diffusion from the wet front to the free surface of the sample. This leads to a mass loss varying with the square root of time (see below), in agreement with some observations [13,15,[18][19][20].…”
Section: Introductionsupporting
confidence: 91%
“…Under this assumption, after some transient stage, the drying rate would be controlled by vapor diffusion from the wet front to the free surface of the sample. This leads to a mass loss varying with the square root of time (see below), in agreement with some observations [13,15,[18][19][20].…”
Section: Introductionsupporting
confidence: 91%
“…In detail, it was also suggested that two FRP should be considered [4,[17][18][19], associated with the continuous and the discontinuous states of the liquid network. The development of a receding dry front was observed and measured in a variety of cases such as experiments with a non-wetting liquid [20], accumulation of ions [21] or particles [22][23] below the free surface, a packing filled with a paste [10], a packing of large beads [23] etc. and in all cases the drying rate in this second regime was probed to scale as the diffusion of vapor from the wet front to the free surface.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of ion concentration can also be determined through their impact on the NMR relaxation time, which for example made it possible to observe the electrodissolution of metal ions (Bray et al 2016). In a similar way, the liquid distribution and deposited particle distribution in time were also obtained in the case of drying of a colloidal suspension in a porous medium (Keita et al 2013(Keita et al , 2016. These data allowed to validate a simple model assuming in that case that each particle exactly follows the liquid path until the liquid evaporates (so that the particle adsorbs to the wall), or the particle is blocked by previously accumulated particles.…”
Section: Transient Liquid Flowsmentioning
confidence: 99%